SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN GURU TERBAIK PADA SMK NEGERI 1 MAJA MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Hary Rizqi Ramadhani; Gunawan Abdillah; Sigit Anggoro (Universitas Majalengka, 2024)
A decision support system is a system using a model that is built to help solve semi-structured problems. The Analytical Hierarchy Process (AHP) method is a method for solving a complex, unstructured situation into several components in a hierarchical arrangement, by giving a subjective value about the relative importance of each variable, and determining which variable has the highest priority in order to influence the outcome. this situation. The results of accuracy testing can be concluded that testing data on civil servant teachers which was carried out by comparing the data of civil servant teachers selected by the principal and using the system obtained an accuracy of 83.3%. In previous research, the Teacher Performance Assessment Team (PKG) was carried out by assuming the importance of each criterion without being given a weight, while the results obtained from system calculations, there was a weight given to each criterion. Testing was carried out on 47 civil servant teacher data with six planned civil servant teachers by the Principal in order to obtain the title of best teacher. Based on the test results, there were two civil servant teachers who were different from the data planned by the Principal, so the level of accuracy of the decision support system for selecting the best teacher using the AHP method was 83.3%.